Adsorbent for treating heavy metal wastewater and preparation method thereof

By γ-ray irradiation of polyacrylamide and Myrtle water extract and loading modified iron tetroxide nanoparticles, an efficient heavy metal adsorbent was prepared, which solved the problems of limited adsorption capacity and difficulty in regeneration of existing adsorbents in high-concentration heavy metal wastewater treatment, and achieved efficient heavy metal adsorption and good regeneration performance.

CN119680524AActive Publication Date: 2025-03-25TIANJIN SEA WATER DESALINATION & COMPLEX UTILIZATION INST STATE OCEANOGRAPHI +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510192866.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The adsorption capacity of existing adsorbents is limited when treating high-concentration heavy metal wastewater and is difficult to regenerate, resulting in a shortened service life.

Method used

A highly efficient heavy metal adsorbent was prepared by γ-ray irradiation of polyacrylamide and Myrtle water extract and loading modified iron tetraoxide nanoparticles.

Benefits of technology

This adsorbent significantly improves the adsorption performance of heavy metals Cd2+, Pb2+ and Hg2+, and has good regeneration properties, and is suitable for the treatment of heavy metal wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an adsorbent for treating heavy metal wastewater and a preparation method thereof, and relates to the technical field of wastewater treatment. The preparation method comprises the following steps: mixing polyacrylamide with a rhodomyrtus tomentosa aqueous extract, and performing gamma-ray irradiation to obtain irradiation modified polyacrylamide; the preparation method comprises the following steps: carrying out modification treatment on Fe3O4 nanoparticles and a rhodomyrtus tomentosa alcohol extract in ethylene glycol to obtain modified Fe3O4 nanoparticles; and then loading the modified Fe3O4 nanoparticles in an organic solvent by using irradiation modified polyacrylamide to obtain the heavy metal adsorbent. The adsorbent shows an excellent adsorption removal effect on heavy metal ions, has good regeneration performance, has the characteristics of simple and convenient preparation process and high operability, and can effectively meet the actual requirements of heavy metal wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to an adsorbent for treating heavy metal wastewater and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization, the discharge of heavy metal wastewater has become a serious environmental problem. Heavy metals such as lead, cadmium, mercury, and chromium are highly toxic, difficult to degrade, and bioaccumulate, posing a serious threat to ecosystems and human health. Therefore, it is particularly urgent to develop efficient heavy metal wastewater treatment technologies. Adsorption has become one of the main methods for treating heavy metal wastewater due to its simple operation, low cost, and wide range of applications. Adsorption is a process that uses the physical or chemical effects on the surface of the adsorbent to selectively adsorb heavy metal ions in wastewater onto its surface, thereby achieving wastewater purification. Its main advantages include: (1) High efficiency: It can effectively remove a variety of heavy metal ions, especially suitable for low-concentration heavy metal wastewater. (2) Low cost: Compared with other treatment methods (such as chemical precipitation, ion exchange, etc.), the adsorption method has simple equipment and low operating costs. (3) Environmental protection: The adsorbent can be recycled to reduce secondary pollution. (4) Strong adaptability: It is suitable for different types of heavy metal wastewater and is insensitive to changes in water quality.

[0003] Common adsorbent types include natural material adsorbents, modified material adsorbents, and new composite material adsorbents. (1) Natural material adsorbents mainly include activated carbon, zeolite, bentonite, chitosan, etc. These materials have rich pore structures and high specific surface areas, and can provide a large number of adsorption sites. (2) Modified material adsorbents modify natural materials by chemical or physical methods to improve their adsorption performance. Common modification methods include acid-base treatment, heat treatment, and loading of metal oxides. For example, acid-base modified activated carbon can increase the surface functional groups of activated carbon and enhance the selective adsorption of heavy metal ions. It is mainly used to improve the adsorption efficiency of specific heavy metal ions (such as chromium and nickel); for example, metal oxide-loaded zeolite can significantly improve the adsorption capacity of heavy metal ions (such as lead, cadmium, and mercury) by introducing metal oxides (such as Fe2O3 and TiO2) to enhance the adsorption activity; for example, magnetic nanoparticles modified bentonite can give the adsorbent magnetism, which is convenient for separation and recovery. It is mainly used for large-scale wastewater treatment and is easy to operate and recycle. (3) New composite adsorbents combine the advantages of multiple materials and have higher adsorption capacity and better mechanical strength. Common composite materials include carbon-based composites, polymer-based composites, metal-organic framework materials (MOFs), etc. Carbon-based composites have high conductivity, good stability and mechanical strength, can be widely used to remove a variety of heavy metal ions, and have excellent regeneration performance; polymer-based composites are highly designable and can adjust their functions according to needs. They are suitable for complex wastewater systems and can remove multiple pollutants at the same time; metal-organic framework materials (MOFs) have highly ordered pore structures and high specific surface areas, and have extremely high selective adsorption capacity for specific heavy metal ions (such as uranium and cobalt).

[0004] Although adsorption has shown many advantages in heavy metal wastewater treatment, it still faces some challenges: 1. Limited adsorption capacity: For high-concentration heavy metal wastewater, the adsorption capacity of the adsorbent may be insufficient, requiring frequent replacement or regeneration. 2 Difficult regeneration: Some adsorbents are easily deactivated during the regeneration process, resulting in a shortened service life. Summary of the invention

[0005] The purpose of the present invention is to provide an adsorbent for treating heavy metal wastewater and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and ensure the adsorption treatment effect of heavy metal wastewater.

[0006] To achieve the above object, the present invention provides the following solutions: The present invention provides a method for preparing a heavy metal adsorbent, which is characterized by comprising the following steps: The polyacrylamide is mixed with the water extract of Myrtle, and subjected to gamma ray irradiation to obtain irradiation-modified polyacrylamide; Fe3O4 nanoparticles and myrtle alcohol extract were modified in ethylene glycol to obtain modified Fe3O4 nanoparticles; The irradiated modified polyacrylamide is loaded on the modified Fe3O4 nanoparticles in an organic solvent to obtain the heavy metal adsorbent.

[0007] As a further preferred embodiment of the present invention, the irradiation energy of the gamma ray irradiation is 3-6 MeV, the irradiation dose is 25-60 kGy, and the irradiation time is 3-8 min.

[0008] As a further preferred embodiment of the present invention, the mass ratio of the polyacrylamide to the myrtle water extract is 10-12:1-3.

[0009] The myrtle water extract is a substance obtained by extracting myrtle with water at 45-60° C.; the myrtle alcohol extract is a substance obtained by heating myrtle with ethanol and refluxing.

[0010] Furthermore, the more preferred preparation steps of the myrtle water extract are as follows: The myrtle was crushed and added into deionized water, and extracted in a water bath with shaking at 45-60°C for 1-2h, and allowed to stand, and the supernatant was taken, and filtered after being cooled to room temperature. The filtrate was allowed to stand, and the supernatant was centrifuged and dried to obtain the myrtle water extract.

[0011] Furthermore, the step of modifying the Fe3O4 nanoparticles is more preferably as follows: a. Wash, dry and crush the myrtle; b. The myrtle treated in step a was added to anhydrous ethanol and heated under reflux for extraction, the reflux time was 2-4h; c. After the reflux extraction is completed, the extract is filtered and separated to remove the residue and insoluble matter; d. The separated extract was transferred to a rotary evaporator and concentrated in vacuum at 40-50°C to remove most of the solvent, and finally the concentrate was dried in a vacuum drying oven to obtain an alcohol extract of myrtle; e. The Fe3O4 nanoparticles were dispersed in ethylene glycol to form a 0.5 g / L suspension, and ultrasonic treatment was performed to make the Fe3O4 nanoparticles evenly dispersed. Then, the myrtle alcohol extract was added to the system in a ratio of Fe3O4 nanoparticles: myrtle alcohol extract = 1:1-3, and the reaction was stirred at 55-60°C for 15-20 minutes to obtain modified Fe3O4 nanoparticles.

[0012] As a further preferred embodiment of the present invention, the temperature of the modification treatment is 55-60° C. and the time is 15-20 min.

[0013] As a further preferred embodiment of the present invention, the mass ratio of the Fe3O4 nanoparticles to the myrtle alcohol extract is 1:1-3.

[0014] As a further preferred embodiment of the present invention, the mass ratio of the modified Fe3O4 nanoparticles to the irradiation-modified polyacrylamide is 5-6:1-2.

[0015] As further preferred embodiment of the present invention, the organic solvent is ethanol.

[0016] The present invention also provides a heavy metal adsorbent prepared by the above preparation method.

[0017] The present invention further provides the heavy metal adsorbent for adsorbing and removing heavy metal Cd in water. 2+ , Pb 2+ and / or Hg 2 + Application in.

[0018] Traditional adsorbents such as activated carbon and zeolite have problems such as high cost and difficulty in regeneration in practical applications. Polyacrylamide, as a high-efficiency flocculant, has good water solubility and film-forming properties, but its adsorption effect on heavy metal ions is limited. The present invention relates to a method of mixing polyacrylamide (PAM) with natural substances for irradiation treatment and using the mixed material as a carrier to modify ferroferric oxide to significantly improve its adsorption capacity for heavy metal ions. The material prepared by the method has a high adsorption capacity for heavy metal Cd 2+ , Pb 2+ and Hg 2+ It has excellent adsorption performance and is suitable for the treatment of heavy metal wastewater.

[0019] The gamma ray irradiation method used in the present invention is suitable for large-scale sample processing and is convenient for industrial large-scale production. The irradiation can induce a cross-linking reaction between polyacrylamide and the natural substance myrtle water extract, thereby significantly improving its adsorption capacity for heavy metal ions.

[0020] Ferroferric oxide (Fe3O4) is a common magnetic nanomaterial, which is widely used in biomedicine, catalysis, environmental remediation and other fields. By alcohol-modifying ferroferric oxide, not only can its physical and chemical properties be significantly improved, but also its application potential in multiple fields can be expanded. This modification method is simple and easy, with low cost. Alcohol modification can improve its dispersibility, stability and reactivity. The functional groups (such as hydroxyl, alkoxy, etc.) formed by alcohol molecules on the surface of nanoparticles can be used as active sites to promote chemical reactions with other substances. The modified nanoparticles of the present invention have stronger adsorption capacity for heavy metals and better chemical stability. After being compounded with modified polyacrylamide, the adsorption performance of the composite material for heavy metals can be guaranteed.

[0021] The present invention discloses the following technical effects: The present invention mixes polyacrylamide (PAM) and the natural substance myrtle water extract and irradiates them, and uses them as the main body to load modified ferrosoferric oxide nanoparticles. The obtained adsorbent exhibits excellent adsorption and removal effect on heavy metal ions and has good regeneration performance.

[0022] The preparation process of the invention is simple and easy to operate, and can effectively meet the actual needs of heavy metal wastewater treatment. DETAILED DESCRIPTION

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0028] The raw materials involved in the embodiments of the present invention are all commercially available products, and their sources do not affect the technical effects of the present invention.

[0029] The myrtle raw material described in the embodiment of the present invention is specifically dried myrtle fruit.

[0030] Example 1

[0031] The preparation process of heavy metal adsorbent is as follows: (1) Extraction of Myrtle Water Extract: The myrtle was crushed and added into deionized water (solid-liquid ratio 1g:10mL), and extracted by shaking in a water bath at 50°C for 2h, and then allowed to stand, and the supernatant was taken, cooled to room temperature and filtered, and the filtrate was allowed to stand, and the supernatant was centrifuged and dried to obtain the myrtle water extract; (2) Polyacrylamide irradiation modification: After polyacrylamide and myrtle water extract were uniformly mixed in a mass ratio of 10:3, γ-ray irradiation was performed to obtain irradiation-modified polyacrylamide; the irradiation energy was 5 MeV, the irradiation dose was 45 kGy, and the irradiation time was 5 min.

[0032] (3) Fe3O4 nanoparticle modification: a. Wash, dry and crush the myrtle; b. The myrtle treated in step a was added to anhydrous ethanol and heated under reflux for extraction (solid-liquid ratio 1g:10mL), and the reflux time was 3h; c. After the reflux extraction is completed, the extract is filtered and separated to remove the residue and insoluble matter; d. The separated extract was transferred to a rotary evaporator and concentrated in vacuum at 45°C to remove most of the solvent, and the concentrate was finally dried in a vacuum drying oven to obtain an alcohol extract of myrtle; e. Fe3O4 nanoparticles were dispersed in ethylene glycol to form a 0.5 g / L suspension, and ultrasonic treatment was performed to make the Fe3O4 particles evenly dispersed. Then, myrtle ethanol extract was added to the system in a ratio of Fe3O4: myrtle ethanol extract = 1:2, and the reaction was stirred at 55°C for 15 minutes to obtain modified Fe3O4 nanoparticles.

[0033] (4) Preparation of heavy metal adsorbents: The modified Fe3O4 nanoparticles prepared in step (3) were dispersed in ethanol, and then irradiated modified polyacrylamide (the mass ratio of irradiated modified polyacrylamide to modified Fe3O4 was 5:2) was added and stirred to obtain a heavy metal adsorbent.

[0034] Example 2

[0035] The preparation process of heavy metal adsorbent is as follows: (1) Extraction of Myrtle Water Extract: The myrtle was crushed and added into deionized water, and extracted by shaking in a water bath at 45°C for 1 hour, and then allowed to stand, and the supernatant was taken, and filtered after cooling to room temperature, and the filtrate was allowed to stand, and the supernatant was centrifuged and dried to obtain the myrtle water extract; (2) Polyacrylamide irradiation modification: After polyacrylamide and myrtle water extract were uniformly mixed in a mass ratio of 12:1, γ-ray irradiation was performed to obtain irradiation-modified polyacrylamide; the irradiation energy was 6 MeV, the irradiation dose was 60 kGy, and the irradiation time was 3 min.

[0036] (3) Fe3O4 nanoparticle modification: a. Wash, dry and crush the myrtle; b. The myrtle treated in step a was added to anhydrous ethanol and heated under reflux for extraction, the reflux time was 2h; c. After the reflux extraction is completed, the extract is filtered and separated to remove the residue and insoluble matter; d. The separated extract was transferred to a rotary evaporator and concentrated in vacuum at 50°C to remove most of the solvent, and the concentrate was finally dried in a vacuum drying oven to obtain an alcohol extract of myrtle; e. Fe3O4 nanoparticles were dispersed in ethylene glycol to form a 0.5 g / L suspension, and ultrasonic treatment was performed to make the Fe3O4 particles evenly dispersed. Then, myrtle alcohol extract was added to the system in a ratio of Fe3O4: myrtle alcohol extract = 1:1, and the reaction was stirred at 55°C for 15 minutes to obtain modified Fe3O4 nanoparticles.

[0037] (4) Preparation of heavy metal adsorbents: The modified Fe3O4 nanoparticles prepared in step (3) were dispersed in ethanol, and then irradiated modified polyacrylamide (the mass ratio of irradiated modified polyacrylamide to modified Fe3O4 was 5:2) was added and stirred to obtain a heavy metal adsorbent.

[0038] Example 3

[0039] The preparation process of heavy metal adsorbent is as follows: (1) Extraction of Myrtle Water Extract: The myrtle was crushed and added into deionized water, and extracted by shaking in a water bath at 55°C for 1 hour, and then allowed to stand, and the supernatant was taken, and filtered after cooling to room temperature, and the filtrate was allowed to stand, and the supernatant was centrifuged and dried to obtain the myrtle water extract; (2) Polyacrylamide irradiation modification: After polyacrylamide and myrtle water extract were uniformly mixed in a mass ratio of 11:2, γ-ray irradiation was performed to obtain irradiation-modified polyacrylamide; the irradiation energy was 4 MeV, the irradiation dose was 45 kGy, and the irradiation time was 5 min.

[0040] (3) Fe3O4 nanoparticle modification: a. Wash, dry and crush the myrtle; b. The myrtle treated in step a was added to anhydrous ethanol and heated under reflux for extraction, the reflux time was 3h; c. After the reflux extraction is completed, the extract is filtered and separated to remove the residue and insoluble matter; d. The separated extract was transferred to a rotary evaporator and concentrated in vacuum at 50°C to remove most of the solvent, and the concentrate was finally dried in a vacuum drying oven to obtain an alcohol extract of myrtle; e. Fe3O4 nanoparticles were dispersed in ethylene glycol to form a 0.5 g / L suspension, and ultrasonic treatment was performed to make the Fe3O4 particles evenly dispersed. Then, myrtle ethanol extract was added to the system in a ratio of Fe3O4: myrtle ethanol extract = 1:2, and the reaction was stirred at 55°C for 18 minutes to obtain modified Fe3O4 nanoparticles.

[0041] (4) Preparation of heavy metal adsorbents: The modified Fe3O4 nanoparticles prepared in step (3) were dispersed in ethanol, and then irradiated modified polyacrylamide (the mass ratio of irradiated modified polyacrylamide to modified Fe3O4 was 6:1) was added and stirred to obtain a heavy metal adsorbent.

[0042] Comparative Example 1

[0043] The only difference from Example 1 is that no myrtle water extract is added during the irradiation process in step (2).

[0044] Comparative Example 2

[0045] The only difference from Example 1 is that in step (3), only the Fe3O4 nanoparticles are modified with ethanol, and the steps are as follows: Steps (1)-(2) are the same as in Example 1; (3) Fe3O4 nanoparticle modification: The Fe3O4 nanoparticles were dispersed in ethylene glycol to form a 0.5 g / L suspension, and ultrasonic treatment was performed to make the Fe3O4 particles evenly dispersed. The reaction was stirred at 55°C for 15 minutes to obtain modified Fe3O4 nanoparticles.

[0046] (4) Preparation of heavy metal adsorbents: The modified Fe3O4 nanoparticles prepared in step (3) were dispersed in ethanol, and then irradiated modified polyacrylamide (the mass ratio of irradiated modified polyacrylamide to modified Fe3O4 nanoparticles was 5:2) was added and stirred to obtain a heavy metal adsorbent.

[0047] Comparative Example 3

[0048] The only difference from Example 1 is that an equal amount of Myrtle alcohol extract is used in step (2) of polyacrylamide irradiation modification. The preparation process of Myrtle alcohol extract is the same as steps ad in Example 1.

[0049] Effect verification example 1

[0050] The heavy metal adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to heavy metal ion adsorption experiments.

[0051] Heavy metals in polluted waters include Cd 2+ , Pb 2+ and Hg 2+ , the specific content is as follows: Cd 2+ 357.2mg / L, Pb 2+ 258.6mg / L, Hg 2+ 246.2mg / L.

[0052] The heavy metal adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 were added to the above polluted water bodies respectively, so that the concentration of the heavy metal adsorbent was 1 g / L, and adsorbed to saturation at 30°C, and the adsorption removal rate of each heavy metal adsorbent for heavy metals was calculated. The results are shown in Table 1.

[0053] Among them, adsorption removal rate (%) = (heavy metal ion concentration before treatment - heavy metal ion concentration after treatment) / heavy metal ion concentration before treatment × 100%.

[0054] Table 1 Adsorption removal rate (%)

[0055] Effect verification example 2 The heavy metal adsorbents saturated with adsorption of Examples 1-3 and Comparative Examples 1-3 were filtered, washed with ethanol, added to 0.15 mol / L acetic acid, stirred for 1.5 hours, filtered out, washed with deionized water until neutral, and adsorbed and removed by the same adsorption removal method as in Effect Verification Example 1 to test the removal efficiency of each heavy metal ion after the adsorbent was regenerated. The results showed that the adsorbent still had excellent heavy metal ion adsorption performance after 5 cycles, and could still meet the use requirements after 6 cycles.

[0056] Table 2 Cd 2+ Removal rate (%)

[0057] Table 3 Pb 2+ Removal rate (%)

[0058] Table 4 Hg 2+ Removal rate (%)

[0059] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a heavy metal adsorbent, characterized in that: The following steps are involved: The polyacrylamide is mixed with the water extract of Myrtle, and subjected to gamma ray irradiation to obtain irradiation-modified polyacrylamide; Fe3O4 nanoparticles and myrtle alcohol extract were modified in ethylene glycol to obtain modified Fe3O4 nanoparticles; The irradiated modified polyacrylamide is loaded on the modified Fe3O4 nanoparticles in an organic solvent to obtain the heavy metal adsorbent.

2. The preparation method according to claim 1, characterized in that: The irradiation energy of the gamma ray irradiation is 3-6 MeV, the irradiation dose is 25-60 kGy, and the irradiation time is 3-8 min.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the polyacrylamide to the myrtle water extract is 10-12:1-3.

4. The preparation method according to claim 1, characterized in that: The myrtle water extract is a substance obtained by extracting myrtle with water at 45-60° C.; the myrtle alcohol extract is a substance obtained by heating myrtle with ethanol and refluxing.

5. The preparation method according to claim 1, characterized in that: The temperature of the modification treatment is 55-60°C and the time is 15-20 minutes.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the Fe3O4 nanoparticles to the myrtle alcohol extract is 1:1-3.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the modified Fe3O4 nanoparticles to the irradiated modified polyacrylamide is 5-6:1-2.

8. The preparation method according to claim 1, characterized in that: The organic solvent is ethanol.

9. The heavy metal adsorbent prepared by the preparation method according to any one of claims 1 to 8.

10. The heavy metal adsorbent according to claim 9 is used to adsorb and remove heavy metal Cd in water. 2+ , Pb 2+ and / or Hg 2+ Application in.

Citation Information

Patent Citations

  • Preparation method of magnetic hectorite composite polymer heavy metal ion adsorbent

    CN113842900A

  • Plant source extract composite flocculation allelopathic algistat as well as preparation method and application of plant source extract composite flocculation allelopathic algistat

    CN114988539A